Original paperCATECHOLAMINES AND β2-ADRENOCEPTOR GENE EXPRESSION BEFORE AND AFTER MAXIMAL INCREMENTAL CYCLE TEST IN YOUNG ICE HOCKEY PLAYERS: RELATION TO WORK PERFORMED - Kochanska-Dziurowicz, A. A.; Janikowska, G.; Bogacz, A.; Bijak, A.; Stanjek-Cichoracka, A.; Mazurek, U.; Gabrys, T. (Biology of Sport, 2013)
The aim of this study was to assess the plasma adrenaline and noradrenaline concentrations as well as whole blood β2-adrenoceptor gene (ADRB2) expression in young ice hockey players before and immediately after exercise in relation to performed work. Nineteen Youth National Team ice hockey players were subjected to the maximal incremental cycloergometer exercise. The test was done in the pre-competitive phase of training. Among many parameters the plasma adrenaline and noradrenaline concentrations and ADRB2 gene expression in peripheral blood mononuclear cells (PBMC) were determined before and after exercise. The average performed work was 3261.3 ± 558.3 J · kg-1 and maximal oxygen consumption (VO2max) for all players was 53.85 ± 3.91 mL · kg-1 min-1. The geometric mean of the ADRB2 gene expression was statistically significantly different before and after exercise (P ≤ 0.05), while adrenaline and noradrenaline levels in plasma significantly increased after exercise. In the analysed group of athletes we found that initial level of plasma noradrenaline correlated with the performed work (r = - 0.55, P < 0.014) and normalized ADRB2 expression before the exercise correlated with the work done by them (r = 0.48, P<0.039). However, no statistically significant correlations were found between the plasma adrenaline or noradrenaline concentrations and ADRB2 gene expression in peripheral blood of the players. The performed work in the maximal incremental exercise test of regularly training young ice hockey players depends on the initial levels of noradrenaline in plasma and ADRB2 mRNA in PBMC.